What evidence-based learning activities help students acquire knowledge, correct confidence in their own knowledge, and accurate self-assessment? - Bosch, Eva; Spinath, Birgit (Learning and individual differences, 2023)
The current study examines the development of higher education students' knowledge, correct confidence in their own knowledge, and accuracy of self-assessment over one semester and if the use of evidence-based learning activities (such as practice testing) is associated with these outcomes. The present study assessed N = 285 university students' use of learning activities, their knowledge, correct confidence, and accuracy of self-assessment five times over the course of a semester in a lecture course. All learning outcomes improved and were explained by learning activity use beyond students' prior knowledge, prior achievement and motivation. Latent profile analyses distinguished five subgroups of students regarding the frequency and combination of learning activity use. Results indicate that students benefitted most from using multiple activities. The study provides evidence that in a realistic learning setting several learning activities contribute to students' knowledge, correct confidence, and accuracy of self-assessment gains. - Educational relevance statement - The study identifies positive changes in various learning outcomes, i.e., knowledge, correct confidence, and accuracy, over the course of a semester in a cohort of university students. It also examines students' learning behavior with a person-centered approach and if students learning behavior adds to the explanation of learning outcomes. The results support the benefits of engaging in many different learning activities beyond individual learning prerequisites. The study adds to current research by combining the study of multiple learning activities in a lecture course and the longitudinal investigation of multiple learning outcomes. The study further reinforces the importance of providing evidence-based activities in higher education.